PEMBELAJARAN KOSA KATA UNTUK MENINGKATKAN PEMAHAMAN BAHASA ARAB SISWA MTS SWASTA FAJRUL IMAN PATUMBAK - Miftahul Falah (Fakultas Agama Islam, 2021)
Learning strategies are used in a series of learning systems that play a very important role in its success. This research is motivated by the variations in the use of learning methods that are carried out by Arabic language teachers at MTs Swasta Fajrul Iman Patumbak to deliver Arabic learning materials to students, so that students are able to master competencies in accordance with existing learning objectives. Where it is known that in learning Arabic students must be able to master four skills. Listening skills, speaking skills, reading skills and writing skills. Of course, here the teacher must master and use methods that are in accordance with the learning material. The type of research that the author does is a qualitative approach. The results of this study are the teacher's Arabic vocabulary learning strategy using grammar translation strategies (Tariqah al-Qawa'id wa al-Tarjamah), direct strategies (al-Tariqah al-Mubasyarah), reading strategies (Tariqah al-qira'ah ), and Audio-Lingual strategy (al-Tariqah al-Sam'iyyah wa al-Syafawiyyah). The obstacles faced by students and teachers during the process of learning Arabic vocabulary include the obstacles faced by teachers are the lack of interest of students in learning Arabic, the weakness of students' learning enthusiasm due to lack of desire to learn Arabic vocabulary, and students do not understand the meaning of the importance of learning Arabic vocabulary, and the lack of Arabic practice. While the obstacles faced by students include lack of mastery of Arabic vocabulary so that it is difficult to pronounce Arabic, difficulty in memorizing Arabic texts and difficulty in compiling sentences using Arabic.